Telco business models at a crossroads: Towards new ways of financing super-fast broadband - Georg Serentschy (Intereconomics, 2012)
The goals of the Digital Agenda for Europe are far from being achieved, and the measures taken so far have not proven to be suffi ciently effective in order to attain European infrastructure and investment targets in a timely manner. Without adequate investment in telecommunications infrastructure, Europe will lose competitiveness compared to the digitally better-equipped world. This article proposes new funding opportunities as well as a number of policy measures to foster investment in electronic communications infrastructure in order to encourage digital modernisation and thus to enhance the EU's international competitiveness.
Keywords: 330; Telekommunikationsnetz; Infrastrukturbedarf; Infrastrukturinvestition; Internationaler Wettbewerb; EU-Staaten